The impact of investor sentiment on the German stock market - Philipp Finter; Alexandra Niessen-Ruenzi; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2011)
This paper develops a broad-based sentiment indicator for Germany and investigates whether investor sentiment can explain stock returns on the German stock market. Based on a principal component analysis, we construct a sentiment indicator that condenses information of several well-known sentiment proxies. We show that this indicator explains the return spread between sentiment sensitive stocks and stocks that are not sensitive to sentiment fluctuations. Specifically, stocks that are difficult to arbitrage and hard to value are sensitive to the indicator. However, we do not find much predictive power of sentiment for future stock returns.
Keywords: G12; G14; 330; investor sentiment; stock returns; German stock market